Influence of 25 MeV Si ions and 25 MeV O ions on the chemical and structural properties of PEEK films. (June 2021) - Li, Hongxia; Yang, Jianqun; Dong, Shangli; Li, Xingji
Poly (ether ether ketone) (PEEK) material can be used in a wide variety of fields, such as the aerospace, automotive, electronics, and nuclear industries. In this research, the irradiation effect of 25 MeV Si ions and 25 MeV O ions on the PEEK films was studied, focusing on the changes in chemical and structural properties. By analyzing surface morphology and microstructure evolution of the PEEK films after 25 MeV Si ion and 25 MeV O ion irradiation, particles were generated on surface of the PEEK after 25 MeV Si ion irradiation and black dots were generated on surface of the PEEK after 25 MeV O ion irradiation. The irradiation reduced the surface roughness of the PEEK films from the atomic force microscopy (AFM) results. The Fourier transform infrared (FTIR) results indicated that the groups and structure of the material were not changed by irradiation. The X-ray photoelectron spectroscopy (XPS) results showed that the contents of the chemical bonds C–C, C=O increased first and then decreased with the increasing of the fluences. The generated free radicals were observed by the electron paramagnetic resonance spectroscopy (EPR) at room temperature and the irradiation degradation mechanisms were analyzed. Thermal properties of the PEEK irradiated by 25 MeV O ions, indicating that a new secondary crystallization peak was found during the cooling stage. Consequently, the low fluences irradiation improves in the viscoelasticity and mechanical properties of PEEK films, while the high fluences irradiation reduces its performance.